Project VeSElkA: abundance analysis of chemical species in HD 41076 and HD 148330. Issue 1 (22nd June 2017) - Khalack, V.; Gallant, G.; Thibeault, C.
Abstract: A new semi-automatic approach is employed to carry out the abundance analysis of high-resolution spectra of HD 41076 and HD 148330 obtained recently with the spectropolarimetre Echelle SpectroPolarimetric Device for Observations of Stars at the Canada–France–Hawaii Telescope. This approach allows to prepare in a semi-automatic mode the input data for the modified zeeman 2 code and to analyse several hundreds of line profiles in sequence during a single run. It also provides more information on abundance distribution for each chemical element at the deeper atmospheric layers. Our analysis of the Balmer profiles observed in the spectra of HD 41076 and HD 148330 has resulted in the estimates of their effective temperature, gravity, metallicity and radial velocity. The respective models of stellar atmosphere have been calculated with the code phoenix and used to carry out abundance analysis employing the modified zeeman 2 code. The analysis shows a deficit of the C, N, F, Mg, Ca, Ti, V, Cu, Y, Mo, Sm and Gd, and overabundance of Cr, Mn, Fe, Co, Ni, Sr, Zr, Ba, Ce, Nd and Dy in the stellar atmosphere of HD 41076. In the atmosphere of HD 148330, the C, N and Mo appear to be underabundant, while the Ne, Na, Al, Si, P, Ca, Ti, V, Cr, Mn, Fe, Co, Ni, Zn, Sr, Y, Zr, Ba, Ce, Pr, Nd, Sm, Eu, Gd and Dy are overabundant. We also have found signatures of vertical abundance stratification of Fe, Ti, Cr and Mn in HD 41076, and of Fe, Ti, V, Cr, Mn, Y, Zr, Ce, Nd, Sm and Gd in HD 148330.